Impact of the localization on disease course and clinical management in spondylodiscitis. (October 2020) - Stangenberg, Martin; Mohme, Malte; Mende, Klaus Christian; Thiesen, Darius Maximilian; Krätzig, Theresa; Schoof, Benjamin; Eicker, Sven Oliver; Dreimann, Marc
Highlights: 9% of spondylodiscitis cases are disseminated infections with multiple localizations. Epidural abscesses and neurological deficits are more often found cervically. Complications and surgical revision rate show no dependence on the localization. Localization of spondylodiscitis does not affect mortality. Abstract: Objectives: Spondylodiscitis is a severe infection of the spine that can take a diverse number of disease courses depending on its localization, resulting in specific therapeutic strategies. This study aims to identify localization specific characteristics and clinical parameters for spondylodiscitis. Methods: A retrospective review was performed of 211 patients from 2013–2018 with proven spondylodiscitis. In total, 33 were cervical, 48 thoracic and 112 lumbar. In 18 patients disseminated infestations of several localizations were found. The patient records were evaluated for clinical and outcome parameters and demographic characteristics. Results: Patient age, Body Mass Index, inpatient and intensive care stay, and inpatient complications did not differ significantly between different infection localizations. C-reactive protein (CrP) levels showed a significantly reduced value in the thoracic area compared to other localizations. For comorbidities, there was a significantly higher prevalence of endocarditis in disseminated and lumbar infestations compared to thoracic and cervical cases. Epidural abscesses showed a highly increased incidence in cervical cases. With a 30-day mortality rate of 12.1% for cervical, 12.5% thoracic, 13.4% lumbar, and 22.2% in disseminated disease, no significant difference was observed. Conclusions: The present study determined that, although the 30-day mortality rate does not differ according to the localization of the infection, specific clinical parameters, such as CrP values or comorbidities, showed localization-dependent differences.